Resounding transcendence: transitions in music, ritual, and religion - Engelhardt, Jeffers; Bohlman, Philip V. (Oxford University Press, 2016)
Pt. 1. Liturgy, performance healing. Ensnare the thief in the house of the wind : negotiating musical routes of baul-ness / Bertie Kibreah ; Transcending boundaries: Javanese Wayang Kulit without the shadows / Sarah Weiss ; Variations for new themes : recent liturgical developments of the major Buddhist festivals in Taiwan / Pi-yen Chen ; Voicing the between in Tunisian S'ambeli / Richard C. Jankowsky -- pt. 2. Culture, identity, soceity. Sounds transcendent : gospel music and the negotiation of proximity in Trinidad / Timothy Rommen ; New Christian music in Indonesia : inculturation in transition / Marzanna Poplawska ; Transforming Christian music, transforming social identity in South India / Zoe C. Sherinian -- pt. 3. Media and technology, transmission and transformation. Technology and the transmission of oral tradition in the contemporary Jewish community / Jeffrey A. Summit ; Music, media, message : transitions in contemporary American Evangelical music / Stephen A. Marini -- pt. 4. Europe, secularity, revival. Sacred poetics and musical politics in post-secular Europe / Philip V. Bohlman ; Arvo Pärt and the idea of a Christian Europe : the musical effects and affects of post-ideological religion / Jeffers Engelhardt ; Byzantine blossom : the monastic revival of Orthodox chant at Mount Athos / Tore Tvarnø Lind